2023
DOI: 10.1097/md.0000000000035767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traditional Chinese exercise on sleep quality: A systematic review and meta-analysis of randomized controlled trials

Haoyu Liu,
Siling Liu,
Lu Xiong
et al.

Abstract: Background: The efficacy of traditional Chinese exercise (TCE)-based interventions in the improvement of sleep quality is controversial. In this systematic review, we aimed to summarize randomized controlled trials (RCTs) that outline the effects of TCE on sleep quality. Methods: Five databases (Web of Science, Embase, PubMed, Medline, and China National Knowledge Infrastructure) were searched for literature published before July 2022. RCTs examining TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Liu et al suggested that TCEs could improve sleep quality in specific populations, holding clinical significance for certain groups. [38] Similarly, Wu et al showed that both TCEs and GAEs, as non-pharmacological and complementary interventions, can enhance sleep quality in older adults, potentially offering clinical benefits. [39] In contrast to the results of this study, Marian et al conducted a control experiment that demonstrated yoga exercise did not result in an enhancement of sleep quality in university students.…”
Section: Effects Of Tces and Gaes On Sleep Disorders In University St...mentioning
confidence: 99%
“…Liu et al suggested that TCEs could improve sleep quality in specific populations, holding clinical significance for certain groups. [38] Similarly, Wu et al showed that both TCEs and GAEs, as non-pharmacological and complementary interventions, can enhance sleep quality in older adults, potentially offering clinical benefits. [39] In contrast to the results of this study, Marian et al conducted a control experiment that demonstrated yoga exercise did not result in an enhancement of sleep quality in university students.…”
Section: Effects Of Tces and Gaes On Sleep Disorders In University St...mentioning
confidence: 99%